Aspek Ekologis dan Determinan Produksi Kopi Arabika Spesialti di Wilayah Dataran Tinggi Sumatera Utara - Jef Rudiantho Saragih (Department of Urban and Regional Planning, Diponegoro University, 2018)
Monoculture farming of arabica coffee plantation does not support environmental sustainability. International market demands arabica coffee product in compliance with an environmentally friendly standard which promotes ecological-based management. This study aims to identify the ecological aspects of specialty arabica coffee cultivation, and to analyze the effect of shade tree population, the use of organic fertilizer, the pruning of coffee crop, land conservation, and the control of coffee berry borer on specialty arabica coffee production. The data of ecological aspect was collected from three regencies in North Sumatera Province, namely Simalungun, North Tapanuli, and Dairi. Production determinant was analyzed concerning farming cultivation in three districts of Simalungun Regency namely Sidamanik, Pamatang Sidamanik, and Dolok Pardamean. The location was determined with multi-stage cluster sampling and the farmer samples with simple random sampling. The ecological aspect was analyzed descriptively while the determinant of arabica coffee production was analyzed with multiple regression method. The result shows that the shaded arabica coffee farming covers only 32% of the total arabica coffee production in the study area with a population of 54 trees/ha. Land conservation conducted by the farmers utilizes coffee fruit mulch (92%), individual terrace (3%), rorak (4%), and bench terrace (1%). The arabica coffee farming system managed by the farmers consists of monoculture (30%), mix farming (24%), shade coffee (32%), and multistrata coffee (14%). The pruning of coffee plants and integrated control of coffee berry borer has a significant effect on specialty arabica coffee production. Land conservation, population of shade tree, and organic fertilizer are an important production determinant on arabica coffee production in the short-term. These three ecological variables play a role to maintain land preservation and support sustainable arabica coffee production in the long-term.